Analisis Efektivitas Pelaksanaan Pendampingan Program Keluarga Harapan Berbasis Pemberdayaan Ekonomi Masyarakat Dalam Meningkatkan Kesejahteraan Sosial Dalam Perspektif Pengembangan Masyarakat Islam - Rohman, Muhammad Afif Syaifur; Faizal, Faizal; Jauhari, Tantowi (Jurnal Ilmiah Ekonomi Islam, 2024)
The Indonesian government has implemented the Family Hope Program since 2007, in an effort to accelerate poverty reduction. PKH companions are one of the determinants of achieving success in programs that are carried out intensively and sustainably. Facilitators are not fully able to resolve problems that exist between KPM PKH or between companions and KPM PKH. The aim of this research is to find out how the implementation of assistance to KPM PKH improves the social welfare of the Adiluwih Village community and what are the supporting and inhibiting factors for the effectiveness of implementing assistance to KPM PKH in Adiluwih Village. This research is field research using qualitative research methods with a descriptive approach. Data collection techniques through observation, interviews and documentation. The results of this research explain that the assistants in implementing PKH in Adiluwih Village have been effective. The research results show that PKH facilitators have effectively implemented empowerment programs for PKH KPMs in the form of; Program to develop interest in learning through Tutoring, Limited Land Utilization Program, and Family Capacity Building Meeting Program (P2K2). As for the supporting factors for the effectiveness of the implementation of mentoring, namely that the companion has good skills in communicating with the community and recipients of PKH assistance because the companion has attended Social Worker education and training and the companion has been certified as a Professional Social Worker, making it easier for the companion to provide understanding and solve problems. problems faced by the community during the process of implementing the Family Hope Program assistance. Meanwhile, the factor inhibiting the effectiveness of the implementation of mentoring is that PKH facilitators find it difficult to allocate their time to each implementation of empowerment program monitoring activities because the assisted area is too large and there are still KPMs who are not present during the socialization of the program being implemented.